2010
DOI: 10.1016/j.physletb.2010.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The axion shield

Abstract: We investigate the propagation of a charged particle in a spatially constant, but time dependent, pseudoscalar background. Physically this pseudoscalar background could be provided by a relic axion density. The background leads to an explicit breaking of Lorentz invariance; as a consequence the process p → pγ is possible and the background acts as a shield against extremely energetic cosmic rays, an effect somewhat similar to the GZK cut-off effect. The effect is model independent and can be computed exactly. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 13 publications
4
32
0
4
Order By: Relevance
“…For instance, in [26] it was analyzed the suppression of charged particles due to the interaction with a pseudoscalar and it was shown that the axion can play the role of a shield for high energy cosmic rays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in [26] it was analyzed the suppression of charged particles due to the interaction with a pseudoscalar and it was shown that the axion can play the role of a shield for high energy cosmic rays.…”
Section: Discussionmentioning
confidence: 99%
“…A DM relic particle candidate must be non-relativistic, must be stable on the cosmological time scale, and must interact weakly with other particles. Some of the possible candidates are: WIMPS [22], axions [23,24,25,26,27], MeV-scalar fields [28,29], technicolor candidates [30,31,32], and ultralight scalar fields [33,34,35,36,37,38]. An ultra-light scalar field is motivated as DM because it can alleviate some of the problems that arise at galactic scale in the standard paradigm of cold DM, namely, the origin of cusped halos [39] and the overproduction of substructure [40].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is the possibility of "radiative" LIV decays e − → e − γ; the momentum threshold being |k 1 | > 4m 2 e /ζ x . This effect will change the energy spectrum of the e + e − pair produced in LIV γ → e + e − decays, but it is suppressed by a power of α and the cross-section must be proportional to ζ x too [51,53,54]. In spite of that axion density in galaxies is very low there might be the regions of relatively dense axion localization ("axion stars" [49]) and to detect them one has to know how in-medium photons and leptons leave those regions.…”
Section: Discussionmentioning
confidence: 99%
“…One may think also of an axion background accumulated by very dense stars like neutron ones or even of bosonic axion stars [49]. Slowly varying axion background or condensed axions can be in principle discovered as such a background induces the high-energy photon decays into dilepton pairs [50] and, in turn, photon emission by charged particles [51,52,53,54]. Another interesting area for observation of parity breaking is the heavy ion physics.…”
Section: Introduction: Possible Physics Of Time-or Space-dependent Psmentioning
confidence: 99%
“…Тем не менее спонтанное нарушение лоренц-инвариантности могло бы появиться как эффект сре-ды после конденсации (почти) безмассовых полей аксионов [2]- [5] на расстояниях, сравнимых с размерами звезд или галактик, в частности возле (внутри) очень плот-ных звезд [6]. Аксионный фон мог бы стать причиной распада высокоэнергетичных фотонов на дилептонные пары [7] и испускания фотонов заряженными частица-ми [8].…”
Section: модель керрола-филда-джекива с границейunclassified